the ANTE-NATAL CARE (ANC) VISITS, DIVERSITY OF FOOD CONSUMPTION, HB LEVELS OF PREGNANT MOTHERS AND NEWBORN WEIGHT, LENGTH DURING THE COVID-19 PANDEMIC: Kunjungan Ante Natal Care (ANC), Keragaman Konsumsi Pangan, Kadar Hb Ibu Hamil dan Berat Badan, Panjang Badan Bayi Baru Lahir Selama Pandemi Covid-19 - Yulia Wahyuni; Mifthah Muliani Lubis; Jelita Martaulina (Universitas Airlangga, 2022)
Background: the covid-19 pandemic has caused restrictions on antenatal care (ANC). In addition, the limited availability of food ingredients to fulfill the nutrition of pregnant women. Lack of health monitoring and inadequate intake of pregnant women have impacted on weight and length of newborns Objectives: to analyze the correlation between the frequency of antenatal care visit (ANC), dietary diversity and Hb levels on pregnant women with weight and length of newborns at the Duren Sawit Healthy Pregnancy Clinic. Methods: The research design be a cross sectional approach. The sampling technique was accidental sampling in order to obtain 60 pregnant women and 60 newborns. Data collection techniques used the ANC questionnaire, Dietary Diversity Score (DDS), easy touch Hb, baby scales and infantometer boards. Results: There were 66.7% of pregnant women who had incomplete ANC visits, the average consumption diversity was good with a score of 8. 15% of pregnant women were classified as anemic. newborn babies are classified as LBW so-and-so many 5%. The average length of newborns is 48.25 cm. Based on the Spearman rank test, it showed that there was a significant correlation between the diversity of food consumption, HB levels and weight of newborns (p=0.015), (p=0.001) with a value of r=(0.46 and 0.52); and there was no relationship between ANC visits with weight on newborns (p=0.79), (r=-0.21). There is a significant correlation between HB levels and length on newborns (p=0.001) with r=0.57 and there is no relationship between ANC visits, diversity of food consumption and length on newborns (p=0.67), (p=0.54) and the value of r (0.34) (0.26) Conclusions: there is no relationship between ANC visits weight and length of newborns, the diversity of food consumption of pregnant women is related to weight of newborns but not to length of newborns. Hb levels on pregnant women are significantly related to weight and length of newborns.